2009
DOI: 10.2964/jsik.19-224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of User Eye Movements during Viewing of Search Engine Results Pages in Web Information Seeking Tasks

Abstract: Web SERP 3 SERP Information/Navigational SERP We used an eye tracking tool to investigate the effect of user-based, task-based, and querybased properties when people performed information seeking behaviors on the Web on the search engine results pages (SERP). For the analysis of the user experimental data, we integrated information from various sources, including eye tracking data, browser logs, and post-interview data. An analysis of the results indicated that the query type has a dominant effect and implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…By observing the eye gazing position on the search engine result page, Cutrell and Guan found that adding information to the contextual snippet significantly improved performance for informational tasks but not for navigational tasks [21]. Takaku et al used the eye-tracker to investigate the effect of these factors such as user-based, task-based, and 7 query-based properties, when people search information on the web [22]. Granka et aI's study focused on the amount of time spending on viewing abstracts in the search engine result page [23].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By observing the eye gazing position on the search engine result page, Cutrell and Guan found that adding information to the contextual snippet significantly improved performance for informational tasks but not for navigational tasks [21]. Takaku et al used the eye-tracker to investigate the effect of these factors such as user-based, task-based, and 7 query-based properties, when people search information on the web [22]. Granka et aI's study focused on the amount of time spending on viewing abstracts in the search engine result page [23].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, more and more researches have been addressed on issues of using eye-tracking technology to facilitate and enhance information retrieval and web search [21][22][23][24][25]. By observing the eye gazing position on the search engine result page, Cutrell and Guan found that adding information to the contextual snippet significantly improved performance for informational tasks but not for navigational tasks [21].…”
Section: Related Workmentioning
confidence: 99%
“…By observing the eye gazing position on the search engine result page, Cutrell and Guan found that adding information to the contextual snippet significantly improved performance for informational tasks but not for navigational tasks [8]. Takaku et al used the eye tracker to investigate the effect of these factors such userbased, task-based, and query-based properties, when people search information on the web [9]. Granka et al's study focused on the amount of time spending on viewing abstracts in the search engine result page [10].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, more and more researches have been reported on using eye tracking technology to facilitate and enhance information retrieval and web search, and analyze web browsing behavior [7][8][9][10][11][12][13]. Toda et al studied users' web browsing behaviors by measuring their eye movements in an experiment using the eye tracker [7].…”
Section: Related Workmentioning
confidence: 99%
“…Snippets provide the abstract of the page or a part of the sentence around the keyword and help users to decide whether the page includes the information they want to know. It is known that snippets are important and useful for users to choose a URL to be clicked (Takaku et al, 2009).…”
Section: Introductionmentioning
confidence: 99%